The Role of Non-Governmental Organizations in the Development of Social Welfare: Theoretical Assumptions in Sociology - Vorevičienė, Jurgita (Jaunųjų mokslininkų darbai, 2016)
The aim of the paper is to analyse theoretical preconditions for functioning of NGOs in social welfare The role of NGOs in social welfare is discussed, the concept of NGOs and their role in social welfare is explained and interpreted drawing on three contextual approaches: the structural functionalism, social conflict theories and P. Bourdieu’s theory of social fields. The structural functionalism and social conflict theories were chosen because they deal with the discussed object at macro level, meanwhile Bourdieu’s theory of social fields allows to combine both, micro and macro, levels. The structural functionalism theory was chosen because it helps investigate society at macro level by symbolically framing all elements of its functions and disfunctions and thus reveal as if two sides of society: the perfect and the desirable, the imperfect and the problematic. This picture of extremes allows to reveal society failings and identify its weaknesses in a structured way seeking to fulfil and restore its need for order. The conflict theory was chosen as a counterweight to functionalism and order denial emphasised by this paradigm, to a strive to look at the object, NGOs, not from the point of view of order but from the point of view of change and conflicts that affect them. Bourdieu’s theory helps identify the agents that function in the field of social welfare and their role, whether they are dominant and dominated, as well as the power of other agents functioning in the same field. According to this theory, capital (social, economic, cultural) is a very important factor because the agents, while fulfilling their functions, can use it for changes and the edevelopmenty of social welfare. Structural functionalism is the paradigm of positive extremes for which modern society is too dynamic and too individualized. The social conflict paradigm helps identify the competing sides in a structured way and make intuitive assumptions about what they are competing for, i.e. identify what power and authority they are competing for. However, this paradigm does not help explain our rather complex modern society the needs, values and attitudes of which are rapidly changing. The interests of three society sectors, the state, the market and the third sector, collide in the field of social welfare, their competion for power is an ongoing process and, depending on the distribution of social, economic and cultural capital, the agents, their power, role and even the location from which they affect citizens’ social welfare may change from dominant to dominated and vice versa.